Colonial products as traditional foods and drinks fueling tourism and preserving culture in Nova Trento (Santa Catarina, Brazil) - Dalri, Aloisio José; Rossini, Diva de Mello (Revista Turismo em Análise, 2022)
Colonial products are foods and beverages processed using traditional techniques adopted by European immigrants who colonized the municipality of Nova Trento (state of Santa Catarina – SC), Southern Region of Brazil. Initially used as a food reserve for farming families, they gained a new application with the advent of tourism, being sought after and consumed by visitors attracted, mainly, by the religious sites common there. This suggests that a greater understanding regarding those products can stimulate its consume and stimulate other activities. This article aims to analyze the potential of colonial products to understand how they contribute to the development of cultural tourism and the preservation of local food heritage. This is a qualitative, exploratory, and descriptive study, with bibliographic research, field research, and non-participant observation, as well as semi-structured interviews with producers, traders, managers, and consumers of colonial products. Data were analyzed in light of categorical-thematic content analysis. The results indicate that colonial products have a close relationship with the sociocultural and territorial context researched, which favors their preservation by the cultural transmission related to the authenticity process. Its cultural, nutritional, and organoleptic attributes, thus, make attracting new audiences, generating economic opportunities, diversifying and spreading tourism in the destination possible, especially if offered in synergy with other local attractions.